Giving the head a hand: Constructing a microworld to build relationships with ideas in balance control - Arnan Sipitakiat (2018)
This work contributes to the major promise of computational technology for learning in making discovery and acquisition of knowledge accessible in new ways and to a wider range of people. The particular focus here is on learning about ideas in Balance Control through observing one's own body motions and programming physical robots to perform balancing acts, such as balancing an inverted pendulum. The study involved two groups of learners, ages 13 to 15, over twelve months. The physical robots have a dual-mode ability that allowed learners to record and observe motions while controlling the robots manually by hand as well as under program control. A custom-made Logo programming environment together with new 2D graphical elements was created. The results not only show examples of Balance Control concepts that emerged, but highlight the learning process that was made accessible only through the computational technology.